Bridging the gap between real estate research and professional practice in Nigeria. Issue 4 (5th May 2021) - Oyedokun, Tunbosun Biodun; Abidoye, Rotimi Boluwatife; Akinbogun, Solomon Pelumi
Abstract : Purpose: Beyond contributing to literature, research findings are expected to reinforce existing best practices while also serving as a springboard for formulating new and more efficient methods of undertaking economic activities. However, academic research is sometimes divorced from implementation and research findings are not always translated into practice. This study, therefore, assesses the impact of real estate research activities and findings on the practice of real estate surveying and valuation in Nigeria as the largest real estate market in Africa. Design/methodology/approach: An online questionnaire survey was conducted to obtain relevant data from Estate Surveyors and Valuers across the country. The survey questions cover reading of academic papers from the field of real estate and the reasons for doing so; whether they have made any changes to their professional practice based on findings from academic papers; and possible barriers to adoption academic research findings in your practice. Mean score ranking and principal component analysis were employed for data analysis. Findings: Out of a total of 61 participants, only 35 have made a change to their professional practice based on findings from academic papers they have read. "Personal development and enlightenment" ranks first on the list of reasons for reading academic papers among the participants while barriers to the adoption of academic research findings relate mainly to education, dissemination and lack of guidance on how to apply research findings. Practical implications: The study demonstrates how findings from real estate research are being applied and identifies possible barriers that must be addressed to improve the level of application and consequently, the value of academic studies. Originality/value: The study provides evidence on barriers to the adoption of academic research and contributes to the global effort to bridge the gap between academia and practice.